Examination of suckling frequency in beef cattle populations - Kovács, Attila Zoltán; Kovács, Zsolt; Zsoldos, Rebeka; Garbacz, Tamás; Csonka, Áron (Animal welfare, Ethology and Housing Systems (AWETH), 2007)
This paper was carried out to study the connection between the mother cows (sucklers) and their calves during the lactation period, by examining suckling as a form of maternal behaviour. The daily suckling frequency was observed in two beef populations. We constructed suckling curves from some measured variables. The dam’s genotype, the age of cows, the sex of calves, and some environmental agents (e.g. temperature) were tested as factors influencing the suckling frequency of calves. The number of suckling (NSM) increased after the animals woke up, and their (daily) peak was reached in the morning hours. Genotype of the dam significantly affected (P < 0.01) the suckling frequency, but the age of the dam did not affect it significantly (P > 0.05). NSM was not affected by the sex of calves and there was a low correlation between the NSM and the weaning weight of calves. The difference between the experimental days was analyzed only in relation to the year or month in both cases (P < 0.01).
Keywords: animal behaviour; suckling frequency; beef cows and calves; Hereford; Red Angus